1999
DOI: 10.1046/j.1524-4741.1999.99016.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cells in the Blood: A Pilot Study

Abstract: The goal of this pilot study was to determine in patients with operable breast cancer the incidence of breast cancer cells present in the blood, the clearance rate after surgical resection of the primary tumor, and the incidence of patients with persistent cancer cells in the blood after the primary tumor was removed. Twenty-one patients with operable breast cancer had 15 ml venous blood obtained twice prior to surgery and after surgery at 2, 4, 8, 12, 24, and 48 hours and also on days 7 and 14. Immunomagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 11 publications
7
33
0
2
Order By: Relevance
“…These cells are present not only in patients with metastatic disease, but also in those whose tumours are apparently localised [30]. This is also observed in breast cancer, where malignant cells seem to spread into the bloodstream in early stages of tumour development [31,32]. Many patients subsequently relapse at distant sites despite adequate local treatment, presumably as a result of undetected spread of the tumour cells before the removal of the primary tumour [30].…”
Section: Discussionmentioning
confidence: 90%
“…These cells are present not only in patients with metastatic disease, but also in those whose tumours are apparently localised [30]. This is also observed in breast cancer, where malignant cells seem to spread into the bloodstream in early stages of tumour development [31,32]. Many patients subsequently relapse at distant sites despite adequate local treatment, presumably as a result of undetected spread of the tumour cells before the removal of the primary tumour [30].…”
Section: Discussionmentioning
confidence: 90%
“…13,14 Nonetheless, approximately one-third of patients fail to clear tumor cells from the blood following removal of primary tumor. 15,16 Only a small fraction of CTC may be viable and able to enter secondary sites by mechanical entrapment or active migration through the endothelial cell layer. [17][18][19][20] Factors supporting extravasation are highly heterogeneous, including platelets; leucocytes; macrophages and factors secreted by them; selectins and their ligands expressed on endothelial cells and tumor cells, respectively; integrins; and fibrin deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Application of these methods may allow for the early detection of cancer when the tumor burden is small and the disease is potentially more curable (5). It has been reported that anti -breast cancer epithelium monoclonal antibodies detected circulating cells in 95% of breast cancer patients before surgery and in 32% of the patients after surgery (8,9). These promising results support the design of feasibility studies that will utilize sensitive molecular techniques to detect circulating breast cancer cells.…”
mentioning
confidence: 99%